2021
DOI: 10.1016/j.ebiom.2021.103391
|View full text |Cite
|
Sign up to set email alerts
|

Endotrophin is associated with chronic multimorbidity and all-cause mortality in a cohort of elderly women

Abstract: Background: The signalling peptide endotrophin is derived through proteolytic cleavage of the carboxyl-terminal during formation of type VI collagen. It is expressed by most descendants of the mesenchymal stem cells lineage, including adipocytes and fibroblasts, and have been proposed to be a central extracellular matrix hormone associated with several age-related diseases. We aimed to assess the association of endotrophin with chronic disease incidence and death in older women. Methods: 5,602 elderly Danish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The major finding of this study is the mediating role of endotrophin in the effect of obesity on CAD in humans. Previous studies reported endotrophin as an important hormone that induces metabolic dysfunction, fibrosis, and inflammation in rodent models [40][41][42]57 , and cross-sectional studies in humans have found that increased circulating endotrophin level was observationally associated with cardiovascular events and all-cause mortality [43][44][45]58 . However, cross-sectional observational studies cannot disentangle cause and consequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major finding of this study is the mediating role of endotrophin in the effect of obesity on CAD in humans. Previous studies reported endotrophin as an important hormone that induces metabolic dysfunction, fibrosis, and inflammation in rodent models [40][41][42]57 , and cross-sectional studies in humans have found that increased circulating endotrophin level was observationally associated with cardiovascular events and all-cause mortality [43][44][45]58 . However, cross-sectional observational studies cannot disentangle cause and consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Endotrophin is produced in multiple tissues, including adipose tissue 40,41 . Endotrophin strongly induces fibrosis and inflammation, and recent evidence suggests that it is involved in obesity-induced metabolic dysfunction [40][41][42][43][44][45] (Fig 4a).…”
Section: Identification Of the Causal Domain Of Col6a3mentioning
confidence: 99%
“…Endotrophin is a cleavage product of the α3 chain of collagen VI [ 10 ]. Since its first identification as a tumor promoting factor [ 11 , 12 ], more and more observations have linked endotrophin to various fibro-inflammatory conditions, including CKD [ [13] , [14] , [15] ]. Serum endotrophin levels independently correlate with mortality in CKD, suggesting that the accumulation of collagen VI and its cleavage product, endotrophin, promote mortality risk associated with CKD [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Karsdal et al. analyzed the association between serum endotrophin levels and various chronic diseases, and discovered that CKD mortality shows the strongest correlation with circulating endotrophin levels [ 15 ]. All the above evidence prompted us to propose endotrophin as a novel target for treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…In an article in EBioMedicine [1], Morten Karsdal and colleagues report the association of circulating levels of a recently described collagen VI cleavage product, referred to as endotrophin, with chronic disease incidence and death in an observational, prospective cohort of elderly Danish women. Participants in this Prospective Epidemiological Risk Factor Study provided fasting blood samples at baseline (n=5,602) and at follow-up (2,094) timepoints.…”
mentioning
confidence: 99%